Microsatellite analysis using a two-step procedure for fluorescence labeling of PCR products - Jouquand, S (BioTechniques, 1999)
A method for fluorescent labeling of PCR products has been developed. This method consists in a two-step procedure in which a first exponential classical PCR is followed by a "linear amplification". This second step relies on incorporation of fluorescent dNTP (dUTP or dCTP) in order to label the product on only one strand. The products can be applied without prior purification directly to a gel on a fluorescence-based automated DNA sequencer, for length and allele determination. The reliability of the results equals those of the classical 32P or fluorescent primer labeling methods, and the method is definitely less costly. Since the interpretation of the results is easier than with the method consisting in a fluorescent dNTP uptake in both strands in a single PCR, the present strategy should prove useful in mapping projects requiring analysis of a large number of microsatellites